Efektivitas Program Peningkatan Pendapatan Asli Daerah (PAD) dalam Menunjang Pelaksanaan Otonomi Daerah di Kabupaten Cilacap - Umar Said; Aini Kusniawati (Jurnal Riset dan Inovasi Manajemen, 2023)
This research is based on the results of preliminary observations that in order to achieve success and effectiveness in the implementation of Regional Autonomy, it is necessary for the Regional Government to be prepared in all fields, including the readiness of human resources to be able to answer the challenges in the implementation of Regional Autonomy. In addition, what is no less important for the implementation of Regional Autonomy to run effectively is how regions can explore and empower existing regional potentials, so that in terms of finance which is the main element in running regional government, independence can be achieved. The method used is a qualitative descriptive research method. The population in this study was 5 people. The sampling technique used a purposive sample technique, thus the sample in this study was 5 people. The data collection technique used a questionnaire. The results of the study are as follows: The Regional Original Income Increase Program in Supporting the Implementation of Regional Autonomy in Cilacap Regency has been effectively implemented through intensification and extensification programs that are quite effective in boosting the increase in Regional Original Income (PAD), and the Central Government's control of programs carried out by the Regional Government in an effort to increase regional income. The obstacles faced are the lack of existing human resources, both in quality and quantity; Frequent changes in higher legal regulations that disrupt the process of collecting regional revenue; Facilities and infrastructure that are still inadequate in carrying out the task of collecting regional revenue; Lack of understanding of laws and regulations on taxes and levies from the community; Weak law enforcement efforts against taxpayers and levy payers Efforts made to overcome obstacles in the program to increase Regional Original Income in supporting the implementation of Regional Autonomy in Cilacap Regency, are In increasing Regional Original Income (PAD) the Cilacap Regency Government has carried out the following: Improving the quality of human resources/collectors through functional training. Conducting research and reviewing regulations in the field of revenue to be adjusted to applicable laws and regulations. Improving facilities and infrastructure in order to support regional revenue collection. Conducting counseling to the community, especially to taxpayers and levy payers